A systems approach to the process dynamics of interpersonal selling in the financial services industry - Van den Berg, J F (Department of Mechanical Engineering, 2023)
The Financial Services Industry (FSI) in South Africa is currently under severe criticism for the quality of service it provides to its customer base. Customer dissatisfaction expressed through individuals, (See Appendix A) consumer bodies and members of parliament has resulted in the draft and approval of three new bills in parliament, which will protect the rights of customers